The Regulation of Tumor Cell Invasion and Metastasis by Endoplasmic Reticulum-to-Mitochondrial Ca2+ Transfer - White, Carl (Frontiers in Oncology, 2017)
Cell migration is one of the many processes orchestrated by calcium (Ca2+) signaling, and its dysregulation drives the increased invasive and metastatic potential of cancer cells. The ability of Ca2+ to function effectively as a regulator of migration requires the generation of temporally complex signals within spatially restricted microdomains. The generation and maintenance of these Ca2+ signals require a specific structural architecture and tightly regulated communication between the extracellular space, intracellular organelles and cytoplasmic compartments. New insights into how Ca2+ microdomains are shaped by inter-organellar Ca2+ communication have shed light on how Ca2+ coordinates cell migration by directing cellular polarization and the rearrangement of structural proteins. Importantly, we are beginning to understand how cancer subverts normal migration through the activity of oncogenes and tumor suppressors that impinge directly on the physiological function or expression levels of Ca2+ signaling proteins. In this review, we present and discuss research at the forefront of inter-organellar Ca2+ signaling as it relates to cell migration, metastasis and cancer progression, with special focus on ER-to-mitochondrial Ca2+ transfer.